Common International Trends in Football Stadium Attendance - Jan van Ours (Tinbergen Institute, 2020)
This paper examines long-term developments in stadium attendance in professional football in the Netherlands. As in many other European countries attendance had a U-shaped development with the lowest numbers in the mid-1980s. The developments in the Netherlands do not seem to have been affected by hooliganism but by socioeconomic factors and developments in recreation. Furthermore, the association with stadium attendance in the English Premier League is very high. This suggests that stadium attendance is affected not only by national developments but also by common international trends in the interest in football matches.
Keywords: C23; Z21; D12; 330; Professional football; stadium attendance; international spillovers